Szellemi potenciál és a műszaki fejlesztés az Északnyugat–Dunántúlon - Dőry, Tibor (Tér és Társadalom, 1997)
For the Nortwest Transdanubian region the development of higher education and research and development is an especially important task, as this is region in Hungary where the largest amount of foreign inward investment was accumulated, following Budapest and the central region. This can provide a possibility for the creation of Hungarian suppliers networks and the utilisation of the results of research and development. The number of researchers and developers per 10 000 inhabitants is 10% less than the countryside average, and the indices of the individual counties lag behind the data of the counties with university centres. The picture is nicer, however, if we look at the amount of development expenditure per one researcher, but it does not change the fact that the share of R+D expenditure from the county GDP in Northwest Transdanubia is only four-fifths of the countryside average. During the past ten years the number of university and college students almost doubled (grew by 86%). Today there are 23 places where university or college education takes place, which is 13.1% of the higher education capacity of Hungary. However, the higher education network of Nortwest Transdanubia is fragmented and there are several newly settled institutions which do not yet have the necessary experiences and traditions. Researches in the research institutes were characterised in the past 5-6 years by declining financing from the state budget, decreasing number of personnel and a shift towards applied sciences. This latter is especially relevant for technical and agricultural researches. Due to this fact, the share of own resources in the financing of the researches was the highest in the former areas. In national comparison, in the award of scientific research grants, the number of OTKA (National Scientific Research Fund) applications is a good indication: Maybe Veszprém can be listed among the significant university-research centres, but all other major scientific centres of the region are among the mediocre centres with universities or bigger colleges. All the educational-research centres of the region combined are equal to the third centre in Hungary, Pécs. The territorial structure of the expenses on technical development shows a very diverse picture in the region. In Veszprém county the amount of Research and Technical Development Fund per person was ten times higher than in the neighbouring Vas county. The western border in this case is no attraction for the knowledge intensive development activity and the location of businesses involved in the sector. In this respect the higher education and academic research base has a much more important role. The number of applied and registered patents across the counties is similar to the case of the Research and Technical Development Fund. The positive end is again Veszprém, while the negatíve one is Vas county. Within the counties mainly those towns are dominant that are home to universities or colleges. Opposite to the opinion of the National Regional Development Concept of Hungary, the establishment of a real regional innovation centre (with science park and links with the national innovation system) should be initiated. This centre could be Győr, on the ground of a real research university and research and development base.